Migration of phthalates from plastic containers into soft drinks and mineral water - Bošnir, Jasna; Puntarić, Dinko; Galić, Antonija; Škes, Ivan; Dijanić, Tomislav; Klarić, Maja, liječnica; Jergović, Matijana; Ćurković, Mario; Šmit, Zdenko (2007)
Summary: The aim of this study was to determine the level of phthalate migration from plastic containers to soft drinks and mineral water and to identify a possible relationship between the amount and type of phthalate migration, type of preservative used, and the pH of the sample.
Bibliografija: 46 jed
Keywords: Ftalati -- Taloženje -- Plastična ambalaža -- Plastične boce -- Piće